EFFECTIVENESS OF CORPORATE SOSIAL RESPONSIBILITY (CSR) TO THE DEVELOPMENT OF MICRO,SMALL AND MEDIUM ENTERPRISES (SMEs) - Dewi Andriany (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The Company always run its business and deals with the community,both the surronding community and the widercommunity ,both the community in a general sense and the business community,including Micro,Small and Medium Enterprises ((MSMEs).